Hubungan Berat Lahir Bayi dengan Pemberian Makanan Tambahan pada Ibu Hamil di Indonesia: Analisis Survei Kesehatan Indonesia 2023: Relationship between Infant Birth Weight and Supplementary Feeding among Pregnant Women in Indonesia - Reza Hanifatus Aini; Abdul Wahab; Emy Huriyati (Amerta Nutrition, 2025)
Background: Low Birth Weight (LBW) is an important indicator of newborn health and can be influenced by various factors, including nutritional status and interventions during pregnancy. The government is working to reduce LBW rates through a supplementary feeding program for pregnant women, providing fortified biscuits and local foods. Objectives: This study aims to analyze the relationship between LBW and the provision of supplementary feeding to pregnant women in Indonesia using data from the 2023 Indonesian Health Survey (SKI). Methods: The research design used was a cross-sectional study with a total sample of 38,142 pregnant women who had complete data on birth weight and the type of PMT received. Data were analyzed sequentially using bivariable analysis, Mantel-Haenszel stratification, and multivariable logistic regression. Results: The bivariable analysis showed that mothers who received PMT biscuits were more likely to give birth to babies with low birth weight than those who did not receive PMT (OR=1.15; 95% CI=1.02-1.30; p-value=0.049). However, after controlling for confounding variables such as maternal nutritional status and education, the relationship was no longer significant (AOR=1.12; 95% CI=0.99-1.26). Meanwhile, local food PMT showed a negative relationship with LBW, although it was not significant. Factors that remained significantly associated with LBW in the multivariate model were KEK nutritional status, maternal education level, economic status, and gestational age. Conclusions: Local PMT has greater potential to reduce LBW incidence. Maternal nutritional status, education level, economic status, and gestational age are stronger predictors and have an impact on the risk of LBW in Indonesia.